Interfacial engineering between SnO2/MAPbI3 by maleate pheniramine halides toward carbon counter electrode-based perovskite solar cells with 16.21% efficiency. (3rd February 2023) - Cao, Duoling; Li, Zuhong; Li, Wenbo; Pei, Ke; Zhang, Xu; Wan, Li; Zhao, Li; Cherevan, Alexey; Eder, Dominik; Wang, Shimin
Abstract : Multifunctional complex molecules (CHM and BHM) were used to passivate interfacial defects, reduce the interfacial energy barrier, induce the orderly growth of perovskite crystals, and improve the PCE of HTL-free C-PSCs. Abstract : Carbon counter electrode-based perovskite solar cells (C-PSCs) are considered among the most promising solar cells due to their excellent stability and low cost. However, the device performance is still unsatisfactory because of numerous defects at the interface between the electron transport layer (ETL) and perovskite (PVK) layer. In this work, we used two novel pheniramine halides containing maleic acid ( i.e., chlorphenamine maleate (CHM) and brompheniramine maleate (BHM)) to modify the SnO2 /MAPbI3 interface. All modifiers can passivate interface defects, reduce interface strain, and enhance device performance. As a result, the champion power conversion efficiency (PCE) values of HTL-free C-PSCs modified with CHM and BHM are 15.47% and 16.21%, respectively, which are much higher than the 13.45% of the control device. Moreover, the unencapsulated BHM-modified device maintains approximately 82.7% of its initial PCE under ambient conditions with 35% relative humidity at room temperature for 800 h. This study provides a new idea for the application of multifunctional complex molecules in high-efficiency and stable C-PSCs.